Trends in Bleeding Events Among Patients With Acute Coronary Syndrome in China, 2015 to 2019: Insights From the CCC-ACS Project - Wang, Xiao; Zhao, Guanqi; Zhou, Mengge; Ma, Changsheng; Ge, Junbo; Huo, Yong; Smith, Sidney C.; Fonarow, Gregg C.; Hao, Yongchen; Liu, Jun; Morgan, Louise; Gong, Wei; et al. (Frontiers in Cardiovascular Medicine, 2021)
Objective: Major bleeding is a common complication following treatment for an acute coronary syndrome (ACS) and is associated with increased mortality. We aimed to explore the temporal trend of bleeding events in relation to changes of therapeutic strategies among patients hospitalized for ACS in China. Methods: The CCC-ACS project (Improving Care for Cardiovascular Disease in China–Acute Coronary Syndrome) is a collaborative initiative of the American Heart Association and the Chinese Society of Cardiology. We analyzed 113,567 ACS patients from 241 hospitals in China from 2015 to 2019. Major bleeding was defined as intracranial bleeding, retroperitoneal bleeding, a decline in hemoglobin levels ≥3 g/dL, transfusion with overt bleeding, or bleeding requiring surgical intervention, and fatal bleeding. Kruskal-Wallis test was used to examine the trend of major bleeding over time. Results: The rate of in-hospital major bleeding decreased from 6.3% in 2015 to 4.7% in 2019 (unadjusted OR 0.74, 95% CI 0.68-0.80, P<0.001). The relative changes were consistent across almost all subgroups including patients with NSTE-ACS and STEMI, although the trend was more pronounced in NSTE-ACS patients. The decrease in bleeding was accompanied by a decrease in use of GP IIb/IIIa inhibitors and parenteral anticoagulation therapy during hospitalization. The annual reduced risk of bleeding (OR 0.91, 95% CI 0.89-0.93) was attenuated after stepwise adjusting for baseline characteristics and antithrombotic treatments (OR 0.95, 95% CI 0.93-0.97), but did not change after adjusting for invasive treatment (OR 0.95, 95% CI 0.93-0.97). Conclusions: There was a temporal reduction in in-hospital bleeding among Chinese ACS patients during the last 5 years, which was associated with more evidence-based use of antithrombotic therapies.